Formigas e bromélias epífitas em um mosaico agroflorestal: padrões ecológicos e rede de interações - Wesley Duarte da Rocha (2016)
The complexity of tropical forest systems is due to multiple interactions between organisms and habitat. These interactions depend on the nature of the organisms involved in different spatio-temporal scales. Some aspects, such as habitat structure, are important to determine the specific composition of communities. The canopy of a tree helps maintaining certain microclimatic and microhabitat conditions favoring the diversity of animals inhabiting it, as well as the epiphytic flora. The intensification of land use has increased the pressure on natural tropical forests, and agroecological systems arrays acquired increasing importance in maintaining biodiversity. Thus, the conservation of biodiversity in areas of agricultural use has become the subject of aseries of studies in landscapes where occur tropical forest remnants. The goal of chapter I was to understand the mechanisms that underlie community structure of arboreal ants, aiming to infer the possible patterns of ant diversity in tropical canopies. Thus, we pointout that the structure of the arboreal ants community is strongly associated with some climatic factors, such as high temperature range and low relative humidity in relation to litter. In Chapter II we evaluated the role of different cocoa agroforestry systems in maintaining the ant community structure and interactions between ants and epiphyticbromeliads. We found that the occurrence of epiphytic bromeliads, regardless of the system and / or scale, maintain a diversity of ants in the canopy of agroforestry systems similar to native forest. Using metrics derived from graph theory, we found a high level of specialization in ant-bromeliads interactions in native forest, with a gradual decreasein specialization correlated to environmental homogenization. Finally, in Chapter III we investigated the effects of structural characteristics of host trees (phorophytes) and canopy over the occurrence of bromeliads and on the network of interactions between ants and bromeliads in forest areas and in agroforestry systems. We show that, for the maintenance of bromeliads and for the interaction network bromeliads/ants in forests oragroforestry, the presence of trees with large canopies is crucial, regardless of plant origin, being native or exotic. However, we emphasize that the gradual introduction by planting of exotic tree species can lead to loss off diversity of native flora and its interactions in agroecosystems over time.